2013
DOI: 10.4103/0971-6203.106600
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of Acuros XB dose calculation algorithm with measurements in predicting doses beyond different air gap thickness for smaller and larger field sizes

Abstract: In this study, dose prediction accuracy of Acuros XB (AXB) dose calculation algorithm beyond air gap thickness (range 2, 4, and 6 cm) in simple inhomogeneous phantoms was investigated. The evaluation of AXB was performed by comparing the doses calculated by AXB with the doses calculated by Anisotropic Analytical Algorithm (AAA) and the measured data for different field sizes (3 × 3, 5 × 5, and 10 × 10 cm2) of a 6 MV photon beam. The dose computation was performed within Eclipse treatment planning system, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…It provides a deterministic solution for the Boltzmann equation, unlike the MC approach, where the solution is achieved stochastically. Acuros XB was shown to be more accurate than AAA and CCC in calculating the dose in regions with complex geometries and heterogeneities 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . Bush et al (10) validated Acuros XB against MC in multi‐slab heterogeneous phantoms with low‐ and high‐density heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a deterministic solution for the Boltzmann equation, unlike the MC approach, where the solution is achieved stochastically. Acuros XB was shown to be more accurate than AAA and CCC in calculating the dose in regions with complex geometries and heterogeneities 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . Bush et al (10) validated Acuros XB against MC in multi‐slab heterogeneous phantoms with low‐ and high‐density heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental dose measurements have been conducted in heterogeneous structures to validate modern TP dose algorithms 10 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 . The size of detectors and, especially, the thickness of its sensitive layer must be as small as possible, due to the steep dose gradient at the media interface.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [15,17] , the AAA was shown to predict the dose higher than the AXB in the low density air gap region. If the AXB is considered to be more accurate than the AAA, the current study showed that the AAA may be overestimating the magnitude of EUD for the lung.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the difference in beam modeling approach within dose calculation algorithms, the discrepancies in their dose predictions exist, especially when photon beam traverses the inhomogenous media before it reaches the tumor. A number of studies [14][15][16][17] have reported the superiority of the AXB over the AAA for dose predictions when heterogeneous media are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation